THERP-CREAM Prediction Method for Failure Probability of Human Factor of Air Traffic Control - ZHANG Jianxiang; GAN Xusheng; WU Yarong; YANG Rui (Hangkong gongcheng jinzhan, 2022)
The human error of air traffic controller is the main cause of the aircraft collision in the air,and it is a difficult problem to effectively predict the failure probability of human factor of air traffic control(AT C).For this,on the basis of technique of human error rate prediction(THERP)and cognitive reliability and error analysis method(CREAM),a hybrid prediction method is proposed for failure probability of ATC human factor.Based on the binary tree model of THERP method,the basic chain of accident development is constructed,and then the triggering probability of human unsafety action is modified based on CREAM method,so as to draw a more accurate probability prediction conclusion.Through the comparative analysis of similar accidents,the key accident impact factors can be identified,and formulate targeted control measures.This paper provides an effective analysis method for studying the failure probability prediction of ATC human factor.